Bimetallic NiCo/CNF encapsulated in a N-doped carbon shell as an electrocatalyst for Zn–air batteries and water splitting. Issue 10 (25th April 2019) - Gebremariam, Tesfaye Tadesse; Chen, Fuyi; Jin, Yachao; Wang, Qiao; Wang, Jiali; Wang, Junpeng
Abstract : Bimetallic NiCo/CNF encapsulated in a N-doped carbon shell (NiCo/CNF@NC) catalyst for application in a Zn–air battery and water splitting has been reported in this work. Abstract : Exploring cheap and efficient electrocatalysts for the oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) as alternatives to precious metal-based electrocatalysts is crucial in energy storage and conversion devices. Herein, we report carbon nanofiber supported NiCo nanoalloys encapsulated in a N-doped carbon, NiCo/CNF@NC catalyst, with multifunctional activities. Benefiting from the unique hybrid structure and synergistic coupling between nanoalloys and N-doped carbon which can effectively inhibit the aggregation and detachment of nanoparticles while generating additional active sites, the resultant catalyst demonstrates remarkable ORR, OER and HER performances. NiCo/CNF@NC displays ORR performance with a comparable onset potential of 1.00 V and superior operational durability than the commercial Pt/C catalyst. Additionally, the NiCo/CNF@NC catalyst exhibits OER activity with an overpotential of 0.40 V at 10 mA cm −2 which is close to that of RuO2 . The Zn–air battery based on the NiCo/CNF@NC catalyst delivers a specific capacity of 764 mA h g −1 Zn with an energy density of 871 W h kg −1 Zn at a current density of 20 mA cm −2 . Moreover, the electrically rechargeable Zn–air battery operates with stable cyclic performance for more than 130 cycles. The water splitting device made of symmetric NiCo/CNF@NC catalyst coated nickel foam (NiCo/CNF@NC/NiF) electrodes has demonstrated an overall water splitting performance of 1.54 V at 10 mA cm −2 at a high catalyst loading of 4.6 mg cm −2 .